Solitary Fibrous Tumor With Myxoid Stromal Change. (July 2015) - Lee, Jin Yong; Park, So Eun; Shin, Soo Jung; Kim, Chul Woo; Kim, Sang Seok; Kim, Kwang Ho
Abstract : Abstract: We report the case of a 46-year-old Korean woman who presented with a 5-month history of a hyperkeratotic plaque on the left palm. On examination, the plaque showed an annular pattern with an umbilicated central nodule and a peripheral palisading induration, which had a verrucous surface. After surgical resection, histopathologic analysis revealed that the tumor was composed of haphazardly arranged spindle cells and displayed a predominantly myxoid appearance in the stroma. The tumor cells were positive for CD34 and bcl-2, but negative for smooth muscle actin and S-100. The clinical manifestation and histopathologic findings were most consistent with a diagnosis of solitary fibrous tumor with myxoid stromal change. There was no evidence of recurrence or metastasis during the 8-month follow-up period. This case highlights the importance of an accurate diagnosis of solitary fibrous tumors, which may have extensive myxoid stromal change, hence mimicking other myxoid-type spindle cell tumors.